1991
DOI: 10.1128/mcb.11.6.3229
|View full text |Cite
|
Sign up to set email alerts
|

The PHO84 gene of Saccharomyces cerevisiae encodes an inorganic phosphate transporter.

Abstract: The PH084 gene specifies Pi-transport in Saccharomyces cerevisiae. A DNA fragment bearing the PH084 gene was cloned by its ability to complement constitutive synthesis of repressible acid phosphatase of pho84 mutant cells. Its nucleotide sequence predicted a protein of 596 amino acids with a sequence homologous to that of a superfamily of sugar transporters. Hydropathy analysis suggested that the secondary structure of the PH084 protein consists of two blocks of six transmembrane domains separated by 74 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
305
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(327 citation statements)
references
References 25 publications
14
305
0
2
Order By: Relevance
“…These data raise questions on the dependency of the fungal phosphate transporter (PT) expression on the Pi concentration. To date, high-affinity PT encoding genes that share homology with the yeast high-affinity transporter PHO84 (Bun-Ya et al 1991) have been identified from three AM fungi: Glomus versiforme (GvPT), Rhizophagus irregularis (GintPT), and Glomus mosseae (GmPT) (Harrison and van Buuren 1995;Maldonado-Mendoza et al 2001;Benedetto et al 2005). These genes are expressed in the ERM, indicating a role in Pi acquisition from the soil, as well as in the intraradical mycelium, IRM (Benedetto et al 2005;Balestrini et al 2007;Tisserant et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These data raise questions on the dependency of the fungal phosphate transporter (PT) expression on the Pi concentration. To date, high-affinity PT encoding genes that share homology with the yeast high-affinity transporter PHO84 (Bun-Ya et al 1991) have been identified from three AM fungi: Glomus versiforme (GvPT), Rhizophagus irregularis (GintPT), and Glomus mosseae (GmPT) (Harrison and van Buuren 1995;Maldonado-Mendoza et al 2001;Benedetto et al 2005). These genes are expressed in the ERM, indicating a role in Pi acquisition from the soil, as well as in the intraradical mycelium, IRM (Benedetto et al 2005;Balestrini et al 2007;Tisserant et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For the complementation assay, the coding sequence of OsPT1 was amplified by PCR and subcloned into the yeast expression vector p112A1NE to create OsPT1-p112A1NE. The construct was transformed into the yeast Pi uptake-defective mutant MB192 (Bun-Ya et al, 1991). MB192-OsPT1 and control cells were grown to the logarithmic phase and then subjected to the yeast nitrogen base liquid medium containing different Pi concentrations (20, 60, or 100 mM) evenly.…”
Section: Functional Complementation Assay Of Ospt1 In Yeastmentioning
confidence: 99%
“…This high-affinity transporter is encoded by the PHO84 gene, which has been cloned and sequenced (4), shown to be derepressible by phosphate starvation, and regulated at the transcriptional level by the PHO regulatory pathway (5,6). Its synthesis is repressed by P i concentrations of >100 µM (6).…”
mentioning
confidence: 99%